New Approaches to Dendritic Cell-Based Therapeutic Vaccines Against HIV-1 Infection - Espinar-Buitrago, Marisierra; Muñoz-Fernández, Ma Angeles (Frontiers in Immunology, 2022)
Due to the success of combined antiretroviral therapy (cART) in recent years, the pathological outcome of Human Immunodeficiency Virus type 1 (HIV-1) infection has improved substantially, achieving undetectable viral loads in most cases. Nevertheless, the presence of a viral reservoir formed by latently infected cells results in patients having to maintain treatment for life. In the absence of effective eradication strategies against HIV-1, research efforts are focused on obtaining a cure. One of these approaches is the creation of therapeutic vaccines. In this sense, the most promising one up to now is based on the establishing of the immunological synapse between dendritic cells (DCs) and T lymphocytes (TL). DCs are one of the first cells of the immune system to encounter HIV-1 by acting as antigen presenting cells, bringing about the interaction between innate and adaptive immune responses mediated by TL. Furthermore, TL are the end effector, and their response capacity is essential in the adaptive elimination of cells infected by pathogens. In this review, we summarize the knowledge of the interaction between DCs with TL, as well as the characterization of the specific T-cell response against HIV-1 infection. The use of nanotechnology in the design and improvement of vaccines based on DCs has been researched and presented here with a special emphasis.